Compact Dual-Band Dual-Polarized Antenna for MIMO LTE Applications - Lila Mouffok; Anne Claire Lepage; Julien Sarrazin; Xavier Begaud (International Journal of Antennas and Propagation)
A system of two dual-band dual-polarized antennas is proposed. It operates in two bands, 700 to 862 MHz and 2.5 to 2.69 GHz, thereby making it suitable for LTE applications. The design is composed of two compact orthogonal monopoles printed close to each other to perform diversity in mobile terminals such as tablets or laptops. For each band, two orthogonal polarizations are available and an isolation higher than 15 dB is achieved between the two monopoles spaced by λ0/10 (where λ0 the central wavelength in free space of the lower band). A good agreement is observed between simulated and experimental results. The antenna diversity capability is highlighted with the calculation of envelope correlation and mean effective gain for several antennas' positions in different environment scenarios.